PERAN KEPALA SEKOLAH DALAM MENUMBUHKAN PERILAKU HIDUP BERSIH DAN SEHAT PADA SISWA SD - Jaka Pasa Tribrata; Abdul Rahim; Taryatman Taryatman; Ardian Arief (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2023)
This research describes the role played by the principal at SDN Air Gegas Muara Beliti in cultivating PHBS in students. Using a qualitative approach. The research was conducted at SDN Air Gegas Muara Beliti. The methods and data sources used were interviews and observations with the principal, homeroom teacher for class V, and students in class V as primary data, while documentation activities became secondary data. Using technical triangulation to check data reliability. Data is analyzed through data collection, data presentation, and making conclusions. The results of the study are 1) School principals use internal meetings to provide direction and guidance to teachers so that they always socialize the importance of PHBS to students. 2) students carry out joint cleaning outside the class 1-2 pickets once a week on Saturdays and carry out good cooperation between related parties or institutions that can have an impact on PHBS activities. 3) students carry out routine gymnastics on Fridays, and students carry out immunizations along with health counseling from the puskesmas. 4) provide direction and guidance to students regarding PHBS and provide an evaluation of each PHBS activity carried out. The leadership role includes setting a good example in actualizing PHBS to students, making positive PHBS-themed activities, and carrying out promotive, preventive, and repressive actions. Then as supervisor, the principal carries out the task of controlling and evaluating each PHBS activity, directing and guiding teachers and students regarding PHBS, motivating in growing PHBS, and building good cooperation among stakeholders and the surrounding community.